2011
DOI: 10.1016/j.tcb.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Rabs and the exocyst in ciliogenesis, tubulogenesis and beyond

Abstract: The exocyst -- an octameric protein complex mediating vesicle tethering at the plasma membrane for exocytosis -- is a downstream effector of the Rab proteins Rab8 and Rab11, which are key regulators of membrane trafficking from the trans-Golgi network and recycling endosome to the plasma membrane. Rab11 and Rab8 coordinate their actions via Rabin8, the guanine nucleotide exchange factor of Rab8. A cascade of protein-protein interactions involving the Rabs and the exocyst complex couples the generation of secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 50 publications
2
98
0
Order By: Relevance
“…Interestingly, the Rab family GTPase Rab11, which regulates recycling endosomes and vesicle trafficking from the trans-Golgi (Das and Guo, 2011), controls cilia length (Knödler et al, 2010) and the sorting and basolateral transport of E-cadherin in mammalian cell cultures (Lock and Stow, 2005). In zebrafish, MO knockdown of Rab11a has been recently shown to reduce KV lumen size (Westlake et al, 2011), similar to the KV phenotype observed in Lgl2 MO embryos.…”
Section: Lgl2 Genetically Interacts With Rab11a To Regulate E-cadherimentioning
confidence: 80%
“…Interestingly, the Rab family GTPase Rab11, which regulates recycling endosomes and vesicle trafficking from the trans-Golgi (Das and Guo, 2011), controls cilia length (Knödler et al, 2010) and the sorting and basolateral transport of E-cadherin in mammalian cell cultures (Lock and Stow, 2005). In zebrafish, MO knockdown of Rab11a has been recently shown to reduce KV lumen size (Westlake et al, 2011), similar to the KV phenotype observed in Lgl2 MO embryos.…”
Section: Lgl2 Genetically Interacts With Rab11a To Regulate E-cadherimentioning
confidence: 80%
“…Exocyst subunits have been detected at the base or inside of primary cilia by immunofluorescence microscopy or EM; inhibition of exocyst function affected ciliogenesis (Rogers et al, 2004;Zuo et al, 2009;Feng et al, 2012). In addition, an interaction network between Rab11, Rabin8 (the guanine nucleotide exchange factor for Rab8), Rab8 and the exocyst complex regulates primary ciliogenesisprobably by mediating the transport of transmembrane proteins or basal bodies to the cilia membrane, although further experimental evidence is needed to support this hypothesis Das and Guo, 2011;Feng et al, 2012). Rab10 also interacts with the exocyst and mediate ciliogenesis in renal epithelial cells, probably through a similar mechanism (Babbey et al, 2010).…”
Section: The Exocyst In Primary Ciliogenesismentioning
confidence: 99%
“…Although studies in yeast and mammalian cells have revealed different types of regulation of Sec2p/Rabin8 by Ypt32p/Rab11 (i.e., membrane recruitment vs. kinetic activation), the Rab cascade serves to coordinate the generation of vesicles from the donor compartments to its subsequent transport and fusion (3,4,19,20). The Rab11-Rabin8-Rab8 signaling cascade is implicated in a number of cell biological processes, such as primary ciliogenesis and cystogenesis (16,17,20,21).…”
mentioning
confidence: 99%